State construction and art in East Central Europe, 1918-2018 - Chmielewska, Agnieszka; Kossowska, Irena; Lachowski, Marcin, 1975- (New York, NY : Routledge, 2023)
"This volume offers a comprehensive perspective on the relationship between the art scene and agencies of the state in countries of the region, throughout four consecutive yet highly diverse historical periods: from the period of state integration after World War I, through the communist era post 1945 and the time of political transformation after 1989, to the present-day globalization (including counter-reactions to westernization and cultural homogenization). With twenty-four theoretically and/or empirically-oriented articles by authors from sixteen countries (East Central Europe and beyond, including the United States and Australia), the book discusses interconnections between state policies and artistic institutions, trends and the art market from diverse research perspectives. The contributors explore subjects such as the impact of war on the formation of national identities, the role of artists in image-building for the new national states emerging after 1918, the impact of political systems on artists' attitudes, the discourses of art history, museum studies, monument conservation and exhibition practices. The book will be of interest to scholars working in art history, cultural politics, cultural history, and East Central European studies and history"--
Cultural specificity of East Central Europe -- Nation- and state-building processes -- Aestheticization of politics-ideologization of aesthetics -- Art exhibitions as a political instrument -- Architecture as vehicle for state cultural policy.
Keywords: Art -- Political aspects -- Europe, Central -- History -- 20th century; Art -- Political aspects -- Europe, Central -- History -- 21st century; Art -- Political aspects -- Europe, Eastern -- History -- 20th century; Art -- Political aspects -- Europe, Eastern -- History -- 21st century; ART / European; ART / History / Contemporary (1945-); ART / History / Modern (late 19th Century to 1945)